Depressive disorders in patients with chronic obstructive pulmonary disease with comorbid course with metabolic syndrome - Evgeny V. Kozlov; Evgeny V. Derevyannykh; Natalia A. Balashova; Alexander G. Ivanov; Roman A. Yaskevich; Evgeny L. Davydov (LLC "MEDIAFORMAT", 2023)
In order to study the indicators of depression in patients with chronic obstructive pulmonary disease (COPD) with a comorbid course with metabolic syndrome (MS), 92 male patients with COPD were examined. The diagnosis of COPD was verified and the severity was assessed in accordance with the criteria of the Global Initiative for Chronic Obstructive Lung Disease (2019). Metabolic syndrome was diagnosed based on the criteria of clinical recommendations of the All-Russian Scientific Society of Cardiology (2009). The presence and severity of depressive disorders were assessed using the CES-D scale (1977). It was found, that regardless of the presence of MS among the men examined depressive disorders of varying severity on the CES-D scale were found in almost half of the examined in both groups with COPD. At the same time among men with MS the number of people with severe depression on the CES-D scale was higher. It was found, that the highest incidence of depression among men with both COPD with MS and COPD without MS was observed among people with IV st. severity and the lowest among patients with II st. respectively.